(untitled) (Foro de Educacion, 2021)
This article presents a Foucauldian and neo-Marxist analysis of the education charity and social enterprise, Teach First. It explores some of the affective, creative, and immaterial practices/technologies whereby this influential organisation creates or fabricates, and attempts to secure, a world of objectivity and meaning, posing and activating corresponding forms of subjectivity and conduct. The analysis addresses some of the diverse forms and modalities of power from which emerges a version of the post-Fordist, neo-liberal teacher subject – an iteration of the teacher characterised by new forms of subjectivity and social relations, which are bound up with changing economic and cultural practices. Moreoever, this article explores Teach First as a form of «affective governmentality», and situates this influential organisation within ongoing, global transformations in the governance of teacher training.